1993
DOI: 10.1088/0268-1242/8/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy growth and characterization of thin (<2 mu m) GaSb layers on GaAs(100) substrates

Abstract: This paper repons the effect of gram parameters and buffer structure on the ILminescence, electrical ano strLctLral character stics of thin (< 2pm)A two-stage SJostrate temperature groffln regime has been oeve oped on the basis of a thermodynam:c consideraton of the growth process, taking 'nto account the additional Gibbs free energy due 10 the strain at the 'nitial growth. Tnis reg'me permits tne grorvtn of GaSb eplayers w:lh a smal Sb/Ga ratio at high substrate temperatures: it provides a greater excaon phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In the case of GaSb buffer layers on GaAs, high densities of threading dislocations form during the coalescence of islands. [17][18][19] The dislocation density decreases as layer thickness increases. Hence, fewer nucleation sites will be available for thicker buffer layers, resulting in less relaxation of the InAs.…”
Section: ͓S0003-6951͑98͒02251-7͔mentioning
confidence: 99%
“…In the case of GaSb buffer layers on GaAs, high densities of threading dislocations form during the coalescence of islands. [17][18][19] The dislocation density decreases as layer thickness increases. Hence, fewer nucleation sites will be available for thicker buffer layers, resulting in less relaxation of the InAs.…”
Section: ͓S0003-6951͑98͒02251-7͔mentioning
confidence: 99%
“…The high lattice mismatch (7.8%) between GaSb epitaxial layer and GaAs substrate hinders the growth of sophisticated device structures. Nowadays, this mismatch is accommodated either via a metamorphic buffer [4][5][6][7] or more recently, by a periodic interfacial misfit (IMF) array growth mode [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The misfit periodicity corresponds to exactly 13 GaSb and 14 GaAs lattice sites. In this way, the strain remains localized at the interface rather than propagating in the vertical direction-dislocations propagate along two directions: [110] and [1][2][3][4][5][6][7][8][9][10]. The GaSb layer is almost completely relaxed with low dislocation density.…”
Section: Introductionmentioning
confidence: 99%
“…19 The concentrations and mobilities at 77K in Table II, where complications due to the type conversion and hopping conduction can be ignored, can be used to compare these samples with the literature values for GaSb grown on semi-insulating substrates. Ivanov et al 20 and Johnson et al 21 are representative of what has been reported for epitaxial GaSb on semi-insulating GaAs substrates. Ivanov et al reported 77 K hole concentrations and mobilities of 1.1x10 16 to 1.5x10 16 cm −3 and 2700 to 4580 cm 2 /Vs while Johnson et al reported 1.5x10 15 to 8x10 15 cm −3 and 756 to 310 cm 2 /Vs at that temperature, to which our values in Table II, 1x10 15 to 2x10 16 cm −3 and 3000 to 7000 cm 2 /Vs, compare favorably.…”
Section: Aip Advances 5 097219 (2015)mentioning
confidence: 77%